2017
DOI: 10.1542/peds.2016-1233
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Cushing’s Syndrome Due to Topical Ocular Glucocorticoid Treatment

Abstract: Iatrogenic Cushing’s syndrome (CS) is a severe adverse effect of systemic glucocorticoid (GC) therapy in children, but is extremely rare in the setting of topical ocular GC therapy. In this article, we report the case of a 9-year-old girl suffering from idiopathic uveitis who developed CS due to topical ocular GC treatment. She was referred to the ophthalmology department with a complaint of painful eyes, at which time she was diagnosed with bilateral iridocyclitis and started on a treatment of betamethasone s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…Plasma prednisolone levels detected in our dogs, albeit relatively small and potentially 50-100-fold lower than other routes of administration (oral, peribulbar or subconjunctival injection) (39-41), are not completely without risk. Topical corticotherapy has been associated with systemic adverse effects in dogs of diverse size and body weight, namely suppression of the hypothalamic-hypophyseal-adrenal axis (up to the development of iatrogenic Cushing's) and hepatic glycogen accumulation (42)(43)(44)(45), with similar concerns being reported in human patients (46,47). Taken together, though topical prednisolone acetate is an excellent drug for inflammatory and immune-mediated diseases of the anterior segment of the eye, caution must be exercised to prevent unwanted and potentially serious adverse effects, regardless of a patient's size.…”
Section: Discussionmentioning
confidence: 94%
“…Plasma prednisolone levels detected in our dogs, albeit relatively small and potentially 50-100-fold lower than other routes of administration (oral, peribulbar or subconjunctival injection) (39-41), are not completely without risk. Topical corticotherapy has been associated with systemic adverse effects in dogs of diverse size and body weight, namely suppression of the hypothalamic-hypophyseal-adrenal axis (up to the development of iatrogenic Cushing's) and hepatic glycogen accumulation (42)(43)(44)(45), with similar concerns being reported in human patients (46,47). Taken together, though topical prednisolone acetate is an excellent drug for inflammatory and immune-mediated diseases of the anterior segment of the eye, caution must be exercised to prevent unwanted and potentially serious adverse effects, regardless of a patient's size.…”
Section: Discussionmentioning
confidence: 94%
“…Up to one fifth of children develop raised intraocular pressure, with onset at weeks or months after starting topical steroids [91,92]. Frequent topical steroids can also lead to growth suppression [93], Cushing syndrome [94] and hypothalamic-pituitary-adrenal axis suppression [95], which in turn can cause adrenal insufficiency. The symptoms and signs of this include: failure to thrive, weakness, hypotension, hypoglycaemia, nausea, vomiting and adrenal crises.…”
Section: Side Effects Of Corticosteroids In Childrenmentioning
confidence: 99%
“…14 To the best of our knowledge, fewer than 10 cases of CS developing following ocular steroid application have previously been reported. [2][3][4][5][6][7][8][9][10] The clinical and hormonal profiles of these cases are summarized in Fluorometholone has been administered in a range of indications. One study reported that allergic conjunctivitis was the second most common indication of fluorometholone use in children.…”
Section: Discussionmentioning
confidence: 99%
“…CS due to topical ocular steroids is very rare. All reported cases of iatrogenic CS were caused by the use of relatively potent steroids, including prednisolone, dexamethasone and betamethasone . Fluorometholone is a modified corticosteroid regarded as having fewer side effects than other steroids.…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation